(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
This study aims to determine the mathematical representation ability of high school students in solving contextual problems in terms of gender differences. This research is a qualitative descriptive study. The data collection was carried out on selected male and female high school class X MIPA 1 students. Data collection techniques used in this study are tests to measure students’ mathematical representations and interview guidelines used are question and answer activities to ahieve research goals. The validity of the data uses the method triangulation. The research subjects includes six students including male and female students with high, medium, and low abilities. The results of this study indicate that male and female subjects with high abilities in general are able to solve problems, female subjects provide more representation than male students; male and female subject with medium ability are able to solve to two problems, female student are more coherent in solving problems and more use verbal representations or written texts; male and female subjects with low ability in general can not solve problems and tend to fabricate in solving problems.